PENGARUH PERSENTASE DAN LAMA PERENDAMAN DALAM LARUTAN KAPUR SIRIH Ca(OH)2TERHADAP KUALITAS KERIPIK PEPAYA (Carica papaya L.) DENGAN VACUUM FRYING - Yunus, Ridhayani; Syam, Husain; Jamaluddin P, Jamaluddin P (Universitas Negeri Makassar, 2017)
This research aims to know the effect of percentage dan long of submersion of solution of whiting Ca(OH)2 towards water level, organoleptic, texture, and colour. This research method using Completely Randomized Design (RAL) factorial with the two factors those are factor of percentage of whiting solution (percentage 0,05%,0,10%, and 0,15%) and factor of long of submersion (10 minutes adn 15 minutes) by 3 repetitive . The research result was processed by using ANOVA variety analysis techniques with DMRT (Duncan Multiple Rate) advanced test. The research result indicated that percentage the solution of whiting of that varied had affect on water content,colour, aroma, texture, taste, hardness , crispness and ΔE * colour alteration. the long of submersion had effect on water content, colour, aroma, texture, taste, hardness, crispness and ΔE * colour alteration. The interaction between percentage of whiting solution and long submersion only influence towards water content, crispness, and ΔE * colour alteration. And no effect on colour, aroma, texture, taste and hardness. Based on the chemical result test, organoleptic test, texture test, and colour test were obtained that the best product with 0.15% whiting solution percentage with 15 minutes the long of submersion